Influência da estrutura da paisagem sobre a produção e qualidade de mel da abelha jandaíra (Melipona subnitida, Apidae: Meliponini) na Caatinga - Felipe Neto, Carlos Antonio Lira (Universidade Federal Rural do Semi-Árido, 2015)
Although the provision of many ecosystem services has proven affected by changes in land cover and land use, the relationship between landscape structure and the production and quality of stingless bee honey has not been studied yet. This work aimed to analyze the influence of landscape structure on the production and quality of honey from the bee Jandaira (Melipona subnitida) in Rio Grande do Norte. To do so, 15 meliponaries were selected in several areas this state, in urban and rural areas and represented by different landscape structures. Land cover was mapped in scales of 300, 1000, 2000 and 3000 meters around each meliponary. Land use was classified based on 6 classes: primary forest, secondary forest, tree crop, diverse land use, water body and urbanized area. Different landscape metrics were then calculated based on these maps, using the programs ArcGIS 10.3 and Fragstats. In each meliponary were randomly selected three colonies of M. subnitida from which a sample of honey was collected. The honey collected was sent to the laboratory for physico-chemical diagnosis (humidity, pH, water activity, reducing sugars, apparent sucrose and acidity) and assessing the sensory properties (color). The condition of the colonies was assessed by measuring the relative volume of brood cells, and honey-pots. Interviews were also performed to the beekeepers to estimate the production of honey and the number of colonies. Honey production and quality and colony condition were then related to the different landscape metrics, using a model selection approach. The results show that the proximity and amount of areas of primary forest have a positive effect on honey quality. Secondary forests had a positive effect on the pH and color of honey and a negative influence over the unused space of the boxes used to rear M. subnitida. The amount of urbanized area around the meliponaries was related negatively with honey humidity and positively with the unused space of the boxes. Hence, our work shows that protect areas of preserved Caatinga and secondary forests are important to build a refuge for pollinators and ensure the current and future provision of ecosystem services
Influence of landscape structure on production and quality of honey bee Jandaira (Melipona subnitida, Apidae: Meliponini) in the Caatinga
Keywords: Bee; Honey; Floral resources; Abelha; Mel; Recursos florais; CIENCIAS AGRARIAS::MEDICINA VETERINARIA